2012
DOI: 10.1007/s10552-012-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast and cervical cancer screening utilization among rural and urban Hispanic and American Indian women in the Southwestern United States

Abstract: Our results provide some evidence that Hispanic and AI women that reside in rural areas of the Southwestern United States have lower rates of breast and cervical cancer screening use compared with their urban counterparts. Special efforts are needed to identify ways to overcome barriers to breast and cervical cancer screening for rural Hispanic and AI women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…24 Research has shown an inverse association between educational attainment and cancer mortality. 25 Several studies also report decreased access to cancer screening and worse outcomes for women in rural areas, 26, 27 although one Chicago study showed an urban disadvantage. 28 …”
Section: Discussionmentioning
confidence: 99%
“…24 Research has shown an inverse association between educational attainment and cancer mortality. 25 Several studies also report decreased access to cancer screening and worse outcomes for women in rural areas, 26, 27 although one Chicago study showed an urban disadvantage. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Spain, cervical cancer screening coverage and the prevalence of abnormal cervical cytology was examined in Catalonia by immigration status in over 1 million women. The study showed that immigrants had higher screening rates than Spanish-born women, but were more likely to have abnormal cervical cytology (2.9 vs. 4.5%), highlighting an increased risk for cervical disease in immigrant populations [77,78]. …”
Section: Health Literacy and Immigration Statusmentioning
confidence: 99%
“…Most screening studies intended to increase cancer screening rates focus on specific vulnerable and marginalized populations known to have low cancer screening rates [2-10], such as: immigrants [11-17], ethnic minorities [2,11,15,18,19], underserved populations [20,21], uninsured [11,18,20], individuals with mental health issues [22-24], indigenous populations [4,15,25,26] and rural residents [15,27,28]. These vulnerable and marginalized populations tend to be localized geographically, resulting in community or neighbourhood level studies designed to inform changes at the local level and to be generalizable to other vulnerable and marginalized populations in other geographic locations.…”
Section: Introductionmentioning
confidence: 99%